Pathogenesis of an experimental mycobacteriosis in an apple snail - Cruz Flores, Cesar (2023)
In this work, we aimed at investigating cell and tissue responses of the apple snail Pomacea canaliculata, following the inoculation of the zoonotic pathogen Mycobacterium marinum. Different doses were tested (10, 20, 65, and 100 M CFU) and the mortality rate was negligible. The histopathogenesis was followed at 4, 9, and 28 days after inoculation. Overt histopathological lesions were consistently observed after the two largest doses only. In the lung, marked hemocyte aggregations, including intravascular nodule formation, were observed within the large blood veins that run along the floor and roof of this organ. Hemocyte aggregations were found occluding many of the radial sinuses supplying the respiratory lamina. Acid-fast bacilli were contained in the different hemocyte aggregations. In addition, hemocytes were observed infiltrating the storage tissue, which makes up most of the lung wall, and the connective tissue of the mantle edge. Additionally, signs of degradation in the storage tissue were observed in the lung wall on day 28. In the kidney, nodules were formed associated with the constitutive hemocyte islets and with the subpallial hemocoelic space, in whose hemocytes the acid-fast structures were found. Electron microscopy analysis revealed the presence of bacteria-containing phagosomes within hemocytes located in the surface zone of the islets. Additionally, electron-dense spheroidal structures, which are likely remnants of digested mycobacteria, were observed in close proximity to the hemocytes’ nuclei. The size attained by the hemocyte nodules varied during the observation period, but there was no clear dependence on dose or time after inoculation. Nodules were also formed subpallially. Some of these nodules showed 2–3 layers with different cellular composition, suggesting they may also form through successive waves of circulating cells reaching them. Nodular cores, including those formed intravascularly in the lung, would exhibit signs of hemocyte dedifferentiation, possibly proliferation, and death. Hemocyte congestion was observed in the hemocoelic spaces surrounding the pallial ends of the renal crypts, and the renal crypts themselves showed de-epithelization, particularly on day 28. The diverse cellular responses of P. canaliculata to M. marinum inoculation and the high resilience of this snail to the pathogen make it a suitable species for studying mycobacterial infections and their effects on cellular and physiological processes.